The Anti-tubercular Activity of Noni Fruitsto Inhibition Growth of Multi Drug Resistant-Tuberculosis Bacteria - Mauliku, Novie Elvinawaty (KnE Life Sciences, 2021)
Multidrug-resistant tuberculosis (MDR-TB) is a tuberculosis infection that is resistant to the treatment at least two of the most powerful anti-tuberculosis drugs, such as Isoniazid and Rifampisin. Increased cases of MDR-TB in morbidity and mortality become obstacles in the control of tuberculosis (TB), thus requiring supportive treatment of natural ingredients that can contribute in the treatment of TB, such a noni fruit. The main objective of this study was extract of noni fruits to inhibition the growth of strain MDR-TB bacteria, and compered it with the anti-TB drugs. The Morinda c. Linn (Noni) fruits was extraced by ethanol (96%). The extract was filtered through whatman No.1 filter paper, evaporated to dryness on a water bath until the solvent evaporated completely and yield of the crude extract. The experiment were divided into 3 groups, i.e.: negative control: group I; positive control: group II; crude extracts noni fruit: group III: combinations of crude extracts noni fruit and anti-TB drugs (K, AK, and OF). Each group was divided into three groups’ doses of 30 mg/ml, 40 mg/ml and 50 mg/ml. The Anti-tuberculosis activities of extracts noni fruit and K, AK, and OF against TB-MDR bacteria were tested by susceptibility test using proportion method in Lowenstein-Jensen (LJ) media.The anti-tubercular activity of noni fruits was determined by the minimum inhibitory concentration (MIC) of the bacterial growth at various doses 30 mg/ml, 40 mg/ml, and 50 mg/ml. The research design used post-test only contol group, and analyzed using analysis of variance and post hoct test. The extracted of Morinda c.Linn (noni) fruits have antitubercular activity to inhibiton of growth MDR-TB bacteria at various doses (p value=0,000). At a dose 30 mg/mlthe mean rate of the growth colonies of MDR TB-bacteria whit the mean rate 59,00 ± 27,81, and at a dose 40 mg/ml was1,50 ± 2,81. While at a dose of 50 mg/ml the bacterial colonies of MDR-TB did not grow in media. The combination of Morinda c.Linn (noni) fruit with anti-tuberculosis drugs, was the smallest groups to inhibit and eliminate MDR-TB bacteria at a dose 30 mg/ml(0,00 ± 00.00). The experimental results confirmed the extracted of Morinda c.Linn (noni) fruits have antitubercular activity as well as anti-TB drugs, and the combination of the extracted of Morinda c.Linn (noni) fruits and anti-TB drugs was the best groups to inhibiton of growth MDR-TB bacteria. Keywords: TB-MDR Bacteria, Morinda c. Linn (Noni), Anti-TB drugs, Anti-tubercular activity, MIC.